2017
DOI: 10.1002/app.44835
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fillers and counterface topography on wear behavior of PTFE polymers for ultrasonic motor

Abstract: Aimed to study the effects of reinforcing or functional fillers on mechanical and tribological properties of PTFE-based friction materials of ultrasonic motor, carbon fibers reinforced PTFE composites modified with different functional fillers with differences in dimension, size, and hardness are fabricated. The tribological performances of PTFE-based friction materials are comparatively investigated under different sliding velocities and normal loads on different surface morphologies, respectively. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 26 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…[1][2][3][4] Nevertheless, driving efficiency and service lifetime of USMs are limited by friction materials, the heart of the motors. [1][2][3][4] Nevertheless, driving efficiency and service lifetime of USMs are limited by friction materials, the heart of the motors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Nevertheless, driving efficiency and service lifetime of USMs are limited by friction materials, the heart of the motors. [1][2][3][4] Nevertheless, driving efficiency and service lifetime of USMs are limited by friction materials, the heart of the motors.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al [13] proposed polyvinylidene fluoride composites as friction material for USMs, and the anti-irradiation property of the material was studied. Wang et al [14] investigated the impact of fillers and counter-face topography on the wear behavior of PTFE polymers for USMs. Song et al [15] investigated the tribological performance of a filled PTFE-based friction material for a USM under different temperature and vacuum degrees, and found that the adhesive wear was prone to take place under high vacuum degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Lv et al [8][9][10][11][12][13][14] researched a series of polymer-based frictional materials, such as polytetrafluoroethylene (PTFE), phenolic resin, and Ekonol composites, and compared their tribological properties under different conditions to provide guidance for selecting frictional materials according to the operating condition. Wang et al [15,16] systematically studied the effect of fillers, topography, temperature, and vacuum on the wear behavior of PTFE composites and found that filling some functional additives could improve the wear resistance of the PTFE matrix. High temperature and pressure strongly affect the wear mechanisms of PTFE-based frictional materials.…”
Section: Introductionmentioning
confidence: 99%